DEVELOPMENT OF IM YUNIC FOR SVA LEARNING DEVICE FOR GRAMMATICAL PROFICIENCY - Ella, Jennibelle R.; Mizunuma, Yukari A. (PEOPLE: International Journal of Social Sciences, 2015)
The study developed the IM YUnIC for SVA in response to a desire to offer an interactive, modern-inspired traditional learning device for teaching subject and verb agreement (SVA) among Grade 7 students. Adopting the descriptive research design, data were obtained from the interview with the cooperating teacher, the classroom observation using the device in two randomly chosen Grade 7 sections composed of 76 students of Nicolas L. Galvez Memorial National High School (NLGNHS) in Bay, Laguna, the test, and the survey. Data were analyzed using both qualitative and quantitative methods. Findings revealed that, based on the teacher’s assessment and periodical test, the students’ level of grammatical proficiency was “developing” with grammar being taught implicitly using teacher-made materials. With its interactive features to enhance knowledge on subject and verb agreement, IM YUnIC for SVA was developed and presented to teachers and students. It earned positive feedback in terms of its appearance, impact, utility, and content. A ten-item test was then administered, and results showed that students mean scores were 5.51 and 5.05, suggesting that students need more practice. Hence, IM YUnIC for SVA may not easily develop students’ grammatical proficiency, but it can offer potential benefits.